Mini-documentaries and the invited gaze: an effective way of cross-cultural communication - Zhuofan, Yang; Jun, Luo; Na, Lin (International communication of Chinese culture, 2023)
The nature of mini-documentary is to be true to the story. But being true is not necessarily the replicate of the original, instead, the director can restructure the story based on the original and make it more artistic and enjoyable for the audience. It would be ideal if viewers from different walks of life can take pleasure in interpreting the film in their own ways. A recap of the documentaries about China both from home and abroad reveals either the bias or superficialness to a large extent. The long-term and systematic representation of the people and stories about China is what we need to shed the bias and the misrepresentations. This paper takes the Looking China Youth Film Project as the case to analyze a cross-cultural communication model that enables the international young filmmakers to experience and know about China.